Perlindungan Hukum Wakaf Produktif di Indonesia: Analisis Putusan Pengadilan Agama Pandeglang Nomor 405/Pdt.G/2023/PA.Pdlg - Sabitaqila Suma Farhaniatussafana; Sheira Syaharani Kuan; Tri Utami; Sawitri Yuli Hartati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal protection of productive waqf in Indonesia by analyzing the normative framework, administrative governance, and judicial considerations applied in the decision of the Pandeglang Religious Court Number 405/Pdt.G/2023/PA.Pdlg. The research employs a normative juridical method supported by a case-based analytical approach to understand how statutory provisions, waqf documentation, and factual findings influence the validation of a waqf asset. The study highlights that the reliability of waqf documents, the transparency of the nadzir’s management, and the consistency of field evidence are central to judicial reasoning in determining the legal certainty of productive waqf. It further identifies that the effectiveness of waqf protection depends on the integration of Islamic legal principles, statutory regulations, and institutional practice. Strengthened administrative systems, professional governance, and harmonized legal interpretation are needed to ensure that waqf assets maintain their perpetual purpose and fulfill their social and economic functions. Overall, the research provides a comprehensive view of how legal certainty is established in productive waqf disputes.